Effects of international institutional factors on earnings quality of banks - Kanagaretnam, Kiridaran; Lim, Chee Yeow; Lobo, Gerald J. (Journal of Banking & Finance, 2014)
We examine the relation between legal, extra-legal and political institutional factors and earnings quality of banks across countries. We predict that earnings quality is higher in countries with legal, extra-legal and political systems that reduce the consumption of private control benefits by insiders and afford outside investors greater protection. Using a sample of banks from 35 countries during the pre-crisis period from 1993 to 2006, we find that all five measures of earnings quality studied are higher in countries with stronger legal, extra-legal and political institutional structures. We also find that banks in countries with stronger institutions are less likely to report losses, have lower loan loss provisions, and higher balance sheet strength during the 2007–2009 crisis period. Our findings highlight the implications of country level institutional factors for financial reporting quality and are relevant to bank regulators who are considering additional regulations on bank financial reporting.